A Novel Perovskite Electron–Ion Conductive Coating to Simultaneously Enhance Cycling Stability and Rate Capability of Li1.2Ni0.13Co0.13Mn0.54O2 Cathode Material for Lithium‐Ion Batteries. Issue 19 (26th March 2021) - Gao, Mingxi; Yan, Chenhui; Shao, Qinong; Chen, Jian; Zhang, Chenyang; Chen, Gairong; Jiang, Yinzhu; Zhu, Tiejun; Sun, Wenping; Liu, Yongfeng; Gao, Mingxia; Pan, Hongge
Abstract: Poor cycling stability and rate capability are two key issues needing to be solved for Li‐ and Mn‐rich oxide cathode material for lithium‐ion batteries (LIBs). Herein, a novel perovskite electron–ion mixed conductor Nd0.6 Sr0.4 CoO3 (NSCO) is used as the coating layer on Li1.2 Ni0.13 Co0.13 Mn0.54 O2 (LNCMO) to simultaneously enhance its cycling stability and rate capability. By coating 3 wt% NSCO, LNCMO–3NSCO exhibits an optimal cycling performance with a capacity retention of 99% at 0.1C (1C = 200 mA g −1 ) after 60 cycles, 91% at 1C after 300 cycles, and 54% at 20C after 1000 cycles, much better than 78%, 63%, and 3% of LNCMO, respectively. Even at a high charge and discharge rate of 50C, LNCMO–3NSCO exhibits a discharge capacity of 53 mAh g −1 and a mid‐point discharge voltage of 2.88 V, much higher than those of LNCMO (24 mA h g −1 and 2.40 V, respectively). Benefiting from the high electronic conductivity (1.46 S cm −1 ) and ionic conductivity (1.48 × 10 −7  S cm −1 ), NSCO coating not only suppresses transition metals dissolution and structure transformation, but also significantly enhances electronic conductivity and Li + diffusion coefficient of LNCMO by an order of magnitude. Abstract : For the first time, a novel perovskite electron–ion mixed conductor Nd0.6 Sr0.4 CoO3 is applied to the modification of Li1.2 Ni0.13 Co0.13 Mn0.54 O2 cathode materials for lithium‐ion batteries, by which the cycling stability and rate capability are simultaneously improved. Nd0.6 Sr0.4 CoO3 coating not only suppresses transition metals dissolution and stabilizes structure, but also improves the electronic conductivity and Li + diffusion coefficient of Li1.2 Ni0.13 Co0.13 Mn0.54 O2 by an order of magnitude.